2022
DOI: 10.1021/acsomega.2c04768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of P-Glycoprotein Transport Cycle Reveals a New Way to Identify Efflux Inhibitors

Abstract: P-glycoprotein (P-gp) is found to be of considerable interest for the design of drugs capable of treating chemoresistant tumors. This transporter is an interesting target for which an efficient approach has not yet been developed in terms of computer simulation. In this work, we use a combination of docking, molecular dynamics, and metadynamics to fully explore the states that occur during the capture of a ligand and subsequent efflux by P-gp. The proposed approach allowed us to substantiate a number of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For the MDR characteristic in malignant neoplasms and many other diseases, ABC transporters plays important role, and influences severely the chemotherapy effects [ 37 , 38 ]. The multi-drug resistance gene MDR1 and its encoded P-glycoprotein (P-gp) were considered to be the most noteworthy mechanisms of MDR [ 39 , 40 ]. Based on our previous and present study, we revealed an important GRP75’s upstream transcriptional regulator, NF-κB [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the MDR characteristic in malignant neoplasms and many other diseases, ABC transporters plays important role, and influences severely the chemotherapy effects [ 37 , 38 ]. The multi-drug resistance gene MDR1 and its encoded P-glycoprotein (P-gp) were considered to be the most noteworthy mechanisms of MDR [ 39 , 40 ]. Based on our previous and present study, we revealed an important GRP75’s upstream transcriptional regulator, NF-κB [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these transporters release drugs such as doxorubicin, paclitaxel, etc. [ 43 , 44 , 45 ]. We also previously noted that an increase in the expression level of ABCB1 is observed in HCT116 cells in response to long-term treatment with Nutlin-3a [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of full-length ASO, the method of conformational search implemented in MacroModel force field-based molecular modeling tool that uses brief MD simulations followed by minimization and normal-mode search steps was used. For structures consisting of 4–6 bases, the LigPrep tool and MacroModel minimization were used using OPLS3e force field with the generation of tautomers and stereoisomers. …”
Section: Methodsmentioning
confidence: 99%